2021
DOI: 10.1007/s40264-021-01066-y
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Ivermectin and Doxycycline Monotherapy and in Combination in the Treatment of COVID-19: A Scoping Review

Abstract: Introduction and Objective Ivermectin (IVM) and doxycycline (DOXY) have demonstrated in-vitro activity against SARS-CoV-2, and have a reasonable safety profile. The objective of this systematic review was to explore the evidence in the literature on the safety and efficacy of their use as monotherapy and combination therapy in COVID-19 management. Methods After prospectively registering the study protocol with the Open Science Framework, we searched PubMed, Google Schol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…[ 49 ] Similarly, a number of studies from developing countries have suggested the efficacy of ivermectin and doxycycline, especially in 2021. [ 50 51 52 ] For this reason, few recent articles mentioned the use of ivermectin and doxycycline in children, but the universal use of this medication is still controversial. We could not find much data for use of casirivimab/imdevimab in children <12 years, as it is yet to be FDA approved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 49 ] Similarly, a number of studies from developing countries have suggested the efficacy of ivermectin and doxycycline, especially in 2021. [ 50 51 52 ] For this reason, few recent articles mentioned the use of ivermectin and doxycycline in children, but the universal use of this medication is still controversial. We could not find much data for use of casirivimab/imdevimab in children <12 years, as it is yet to be FDA approved.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that the evidence was not strong enough to either promote or refute their efficacy in COVID-19 management. [ 50 ]…”
Section: Discussionmentioning
confidence: 99%
“…It has many advantages, including the simplification of authorization procedures and the speed of being placed on the market at much lower costs (Jourdan et al, 2020). The most affordable alternative method for discovering the treatment of COVID-19 is the repositioning of existing drugs that are potentially active against SARS-CoV-2 (Akilesh et al, 2021;Bhowmick et al, 2021;Gatti and De Ponti, 2021).…”
Section: Repositioning Of Known Drugsmentioning
confidence: 99%
“…These drugs are supposed to work upon different elements in the disease pathophysiology, and these correspond to two primary therapeutic classifications: drugs that inhibit the viral activity (e.g., favipiravir, remdesivir, azithromycin, lopinavir-ritonavir, hydroxychloroquine) and drugs that modulate the antiviral immune reaction in the host (e.g., corticosteroids, interferons, tocilizumab). Along with these, other agents have been investigated in the management of COVID-19: ivermectin -an antiparasitic agent, and doxycycline -a broad-spectrum tetracycline antibiotic (Bhowmick et al, 2021). In a trial reported by the ISRCTN Registry and ClinicalTrials.gov, WHO specialists used four known antiviral drugs that could potentially affect mortality for patients with COVID-19.…”
Section: Repositioning Of Known Drugsmentioning
confidence: 99%
“…So far, there is no effective antiviral therapy to treat for SARS-CoV-2 infection and COVID-19. Although along the whole COVID-19 pandemic numerous reports have been published describing the potential use of attractive drugs such as ivermectin, doxycycline, hydroxychloroquine, azithromycin, and remdesivir (Yates et al, 2020;Mcfee, 2020;Bhowmick et al, 2021), yet there is controversial of using any of these attractive drug candidates either as monotherapy or in combination. This work by Tan et al penlights their potential use for the treatment of COVID-19 giving new insights into the generation of more effective drug combinations or new formulations against viral infections.…”
mentioning
confidence: 99%